Bibliometric Analysis of Islamic Multicultural Education and Trends in Religious Moderation in 21st Century Education - Wahid, Rahman; Purhasanah, Siti; Munawaroh, Rahmah Zaqiyatul; Indiarsih, Melyana; Kurniadin, Didin (International Journal of Educational Qualitative Quantitative Research, 2023)
In the 21st-century, it is increasingly easy for individuals to interact with each other, so meetings between individuals from various backgrounds, be it religion, race, ethnicity, or ideology. Therefore, the study of Islamic multicultural education and religious moderation is essential to minimize problems and conflicts arising from the reality of increasing diversity. This study aims to analyze the theme of Islamic multicultural education in the trend of religious moderation in the 21st-century education era. This study uses a bibliometric analysis method to see trends, links between keywords, and topics widely studied regarding Islamic multicultural education in the trend of religious moderation. Data sources were obtained from searching for scientific articles in accredited journals. The study results show a trend in research on Islamic multicultural education in the trend of religious moderation in the 21st-century education era. There has also been a shift in the topic of study from this theme in recent years. In addition, several keywords are also interrelated in research with the theme of Islamic multicultural education on the trend of religious moderation. Islamic multicultural education and religious moderation in 21st-century education are expected to realize an inclusive, just, and tolerant social order. Religious moderation and Islamic multicultural education are two prominent movements representing the 21st-century's social and spiritual development. The contribution of this research is to provide an overview of the trend of Islamic multicultural education and religious moderation in adapting to changes that occur in society, both in academic and practical contexts.